Pengaruh Rasio Solvabilitas Dan Ukuran Perusahaan Terhadap Market Value Pada Saham Jakarta Islamic Indeks (JII) - Wahyuni, Komang Tri (Widya Balina, 2023)
This study is conducted to analyze the impact of size, solvability ratio on value of the firm. Variable of capital structure are represented by debt to equity ratio (DER), debt to asset ratio (DAR) and Market to Long term Leverage (MLLEV The samples of this study are JII (Jakarta Islamic Index) companies listed on the Indonesian Stock Exchange (IDX) for the periode 2020-2022. Total Observation of 60 was determined by purposive sampling method. Both market value ratios measured by : PER and PBV. There is a market capitalization variable as a control variable. This study uses Ordinary Least Square (OLS) for hypotheses testing The results show that DER and SIZE have a positive effect with statistical significance on market value (PBV) and unsignificance tested by PER. Ratio MLLEV has effect significance on market value and DAR has significance on market value measured by PER and no significance measured by PBV. The implication of this study showed that all companies should concern of the solvability ratios and consider to use size as decision when increasing the debt in order to make the firm of market value persistantly.